ANALISIS KEPUASAN RUMAH TANGGA PENERIMA MANFAAT RASKIN DI DKI JAKARTA - Rini Andrida; Setiadi Djohar; Idqan Fahmi (Jurnal Manajemen & Agribisnis, 2011)
Aiming to investigate the satisfaction level of household beneficiaries towards Raskin Program, the study attempts to determine the gap between households’ expectation and Raskin Program performance of each satisfaction attribute. By collecting data from 125 respondents of legal beneficiaries, the primary data is processed using descriptive and survey method through questionnaires and interviews and gathered using convenience sampling (non probability sampling). The objectives of the study are to: (1) analyze household’s perception and satisfaction index of Raskin Program; (2) analyze factors that influence household’s satisfaction towards Raskin Program; (3) analyze the official perception of Raskin Program performance; (4) analyze the gap between households’ expectation and Raskin Program performance; and (5) formulate strategy to increase Raskin Program effectiveness.The study has shown significant contribution of all dimensions in influencing customer satisfaction. The application of Gap Analysis has revealed the fact that there is a significant gap in tangible dimension, with reliability dimension is having the largest contribution, sequentially followed by tangible, responsiveness, assurance and empathy dimension with the least contribution. This implies that the priority of factors to be improved is also.   Keywords: Raskin, Household beneficiaries Satisfaction, Effectiveness, Gap Analysis, and Customer Satisfaction Index.